2018
DOI: 10.1111/resp.13314
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusion and outcomes in acute pulmonary embolism

Abstract: RBC transfusion in patients hospitalized with acute PE is rare and appears to be associated with increased risk of short- and long-term mortality, independent of Hb level on admission. This finding underscores the need for future randomized controlled studies on the impact of RBC transfusion in the management of patients admitted with acute PE. [Correction added on 4 May 2018, after first online publication: the word 'serum' was changed to 'plasma' throughout the article where appropriate.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Second, the variables that were included had Pvalues <0.05 and were mostly recognized predictors of mortality in pulmonary embolism (PE) in previous studies. [1][2][3] The incorporation of various haemodynamic parameters (heart rate, blood pressure etc.) into a single variable (simplified PE severity index (sPESI)-a well-validated prognostic score in PE) was specified a priori to avoid overfitting the multivariable model.…”
Section: From the Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the variables that were included had Pvalues <0.05 and were mostly recognized predictors of mortality in pulmonary embolism (PE) in previous studies. [1][2][3] The incorporation of various haemodynamic parameters (heart rate, blood pressure etc.) into a single variable (simplified PE severity index (sPESI)-a well-validated prognostic score in PE) was specified a priori to avoid overfitting the multivariable model.…”
Section: From the Authorsmentioning
confidence: 99%
“…Wong et al . reported that in patients with acute pulmonary embolism (APE), red blood cell (RBC) transfusion is associated with higher mortality, independent of haemoglobin level.…”
mentioning
confidence: 99%
“…It also carries risks of adverse effects and major costs.In a recent publication in Respirology, Wong et al present a single-centre retrospective analysis of the effect of RBC transfusion and mortality on patients hospitalized between 2000 and 2012 with a primary diagnosis of acute pulmonary embolism (PE). 1 They report increased 30-day and 6-month mortality of 19% and 40%, respectively, in 73 (5%) transfused patients, compared with 4% and 10% in the 1303 nontransfused patients. This was reported as an odds ratio for mortality of 3.06 (95% CI: 1.17-8.01) at 30 days and a hazard ratio of 1.97 (95% CI: 1.12-3.46) at 6 months.…”
mentioning
confidence: 94%
“…In a recent publication in Respirology, Wong et al . present a single‐centre retrospective analysis of the effect of RBC transfusion and mortality on patients hospitalized between 2000 and 2012 with a primary diagnosis of acute pulmonary embolism (PE) …”
mentioning
confidence: 99%
“…However, recent conflicting evidence suggests that a single measure of baseline haemoglobin on admission for acute PE may not be predictive of mortality after taking into account the impact of blood transfusions 4. Haemoglobin fluctuations and variability have been explored in other diseases, such as chronic heart failure, end-stage renal failure and malignancy; these studies showed that persistent anaemia or declining haemoglobin trends were associated with poorer outcomes 5–12.…”
Section: Introductionmentioning
confidence: 99%